Establishing peer support services for renal patients: a Welsh experience. (2nd May 2022) - Popham, Joanne; O'Leary, Catherine; Mikhail, Ashraf
Abstract : Patients with chronic kidney disease would benefit from peer support. The authors describe their experience in establishing the service in Wales. The essential requirements for establishing the service are explained. In addition to identifying suitable staffing, a structured and accredited training program for mentors is essential for the success and maintenance of the service. Formal training enables peer mentors to develop their listening skills, communicate effectively and clearly with mentees and identifies ways to deal with any challenging scenarios the mentor may face while providing their peer support. Policies to retain and reward mentors for their contribution are essential to sustain the service, develop the mentor's skills and expand the service that is not currently recognised or funded by healthcare providers. This article provides an outline of the process required to establish an active and long-term peer support programme, based on our local experience in south west Wales. The authors conclude by providing some quotes from their current mentors, describing how rewarding their involvement in the support process has been and summarising key elements needed to sustain an active peer support service and vision for future development.